Sustainable Development Report 2021 - Sachs, Jeffrey (Social Sciences, 2021)
The Sustainable Development Report 2021 features the SDG Index and Dashboards, the first and widely used tool to assess country performance on the UN Agenda 2030 and the Sustainable Development Goals. It contains insights on sustainable development and the impact of COVID-19 on the SDGs. This title is available as Open Access on Cambridge Core.